The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jat.1520
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in the kidney of rats treated with V and/or Mg in drinking water

Abstract: Spontaneous and stimulated lipid peroxidation (LPO) after vanadate and magnesium treatment was studied in kidney supernatants obtained from outbred 5-month-old, albino male Wistar rats. The 2-month-old animals daily received: group I (control), deionized water to drink; group II, water solution of sodium metavanadate, NaVO(3) (SMV, 0.125 mg V ml(-1)); group III, water solution of magnesium sulfate, MgSO(4) (MS, 0.06 mg Mg ml(-1)); and group IV, water solution of SMV-MS at the same concentrations as in groups I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…All details concerning the methodology of determination of LPO and the preparation of kidney homogenates and supernatants for the renal MDA k and TAS k measurements had already been provided [2, 3]. The results of both the OS markers mentioned are expressed as % of control and illustrated in Figure 4(a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All details concerning the methodology of determination of LPO and the preparation of kidney homogenates and supernatants for the renal MDA k and TAS k measurements had already been provided [2, 3]. The results of both the OS markers mentioned are expressed as % of control and illustrated in Figure 4(a).…”
Section: Methodsmentioning
confidence: 99%
“…Its prooxidant action has been demonstrated in in vivo and in vitro conditions [27]. It has been shown that the free radical process-lipid peroxidation (LPO), which is a biochemical biomarker of cellular dysfunction and an index of cytotoxicity [8], is enhanced by V in the kidney [3, 8]. It has also been suggested that LPO may be predictive of renal dysfunction [8].…”
Section: Introductionmentioning
confidence: 99%
“…The daily intake of water and the solutions of SMV, MS, and SMV-MS were measured with a measuring cylinder and the water and fluid intake was expressed as mL/rat/24 h. In turn, the daily intake of V and Mg in the SMV- or/and MS-administered animals was estimated on the basis of the 24 h consumption of the SMV, MS, and SMV-MS solutions and expressed as mg/kg b.wt./24 h. However, the food intake was calculated on the basis of the 24 h consumption of food by the rats from all the groups (the remainder of food together with additional spillage was weighed and subtracted from the whole food that the rats received to eat) and expressed as g/rat/24 h. The V and Mg concentrations in drinking water were selected on the basis of our previous experiments conducted in a rat model [11, 12, 36] and studies of other researchers [37, 38]. The concentration of V was chosen to reveal its prooxidant potential, which was meant to be attenuated by the administration of this element in combination with Mg.…”
Section: Methodsmentioning
confidence: 99%
“…However, in some conditions Mg may stimulate LPO causing OS. Its ability to elevate LPO has been revealed by us [11, 12] and by some other investigators [27]. …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation